2020
DOI: 10.1101/2020.03.24.004382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Practical and effective diagnosis of animal anthrax in endemic low-resource settings

Abstract: 23Background: Anthrax threatens human and animal health, and people's livelihoods in 24 many rural communities in Africa and Asia. In these areas, anthrax surveillance is 25 challenged by a lack of tools for on-site detection. Furthermore, cultural practices and 26 infrastructure may affect sample availability and quality. Practical yet accurate diagnostic 27 solutions are greatly needed to quantify anthrax impacts. We validated microscopic and 28 molecular methods for the detection of Bacillus anthracis in fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An ongoing PCR test was produced for the quick identification of B. anthracis [16,20,38]. Field arranged blood smears were verified by microscopy using four recoloring strategies, including PCR trailed by Bayesian latent class investigation [39]. Samples were tested using a 31-marker multilocus variable-number tandem repeat analysis (MLVA) to identify different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing PCR test was produced for the quick identification of B. anthracis [16,20,38]. Field arranged blood smears were verified by microscopy using four recoloring strategies, including PCR trailed by Bayesian latent class investigation [39]. Samples were tested using a 31-marker multilocus variable-number tandem repeat analysis (MLVA) to identify different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The NCA was chosen for our study as it is known to be hyperendemic for anthrax 4 , 17 , 20 . In addition, informal consultations we held prior to the study, as well as tailored data collection at the community and household level, indicated that local communities have a good understanding of the disease in humans and animals, and of practices around carcass and livestock management that increase risks, particularly in certain locations and periods of the year 24 .
Figure 1 Locations of participatory mapping.
…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, several nucleic acid-based assays targeting anthrax toxin genes have been optimized for the reliable, quick, specific and sensitive identification of organisms causing anthrax. However, these require expertise, expensive devices, heavy infrastructure laboratories and complicated protocols [9], thus are unsuitable for routine laboratories. The Loop-mediated isothermal amplification (LAMP) assay is preferred over other nucleic acid-based assays because it is fast, less labor-intensive and does not require any sophisticated equipment or skilled personnel, and is suitable for the applications at field level and routine laboratories [10].…”
Section: Introductionmentioning
confidence: 99%